2004
DOI: 10.1090/s0025-5718-04-01651-5
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the discrete maximum principle for an elliptic finite element problem

Abstract: Abstract. There has been a long-standing question of whether certain mesh restrictions are required for a maximum condition to hold for the discrete equations arising from a finite element approximation of an elliptic problem. This is related to knowing whether the discrete Green's function is positive for triangular meshes allowing sufficiently good approximation of H 1 functions. We study this question for the Poisson problem in two dimensions discretized via the Galerkin method with continuous piecewise lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 15 publications
0
81
0
Order By: Relevance
“…The present result is based on the analysis of the discrete Green's function (DGF) for higher-order elements. A similar concept was used in the piecewise-linear case in [5]. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The present result is based on the analysis of the discrete Green's function (DGF) for higher-order elements. A similar concept was used in the piecewise-linear case in [5]. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…where C > 0 is independent of the meshsize h. In [8], positivity for discrete Green's function was investigated for Poisson equations. The authors addressed the question of whether the discrete Green's function is positive for triangular meshes allowing sufficiently good approximation of H 1 functions.…”
mentioning
confidence: 99%
“…The discrete maximum principle is also of interest to avoid negative numerical values of typical positive physical quantities like concentration, temperature (in Kelvins), density, and pressure. A single obtuse triangle in the partition can destroy the discrete maximum principle [22,78] It can easily be shown that each nonpositive continuous function f = 0 whose support does not intersect the supports of the finite element functions that vanish at v 1 gives rise to an approximation u h of u that is positive at v 2 , hence violating the discrete maximum principle. It should be mentioned that an alternative approach to enforcing the validity of discrete maximum principles is to modify the finite element method in such a way that obtuse angles do not stand in their way anymore.…”
Section: Applications In Numerical Mathematicsmentioning
confidence: 99%